THE EFFECT OF PLYOMETRIC EXERCISES ON DEVELOPING THE EXPLOSIVE POWER OF THE LEGS, SOME BIOMECHANICAL VARIABLES, AND THE ACCURACY OF STRIKING FROM THE BACK AREA IN VOLLEYBALL FOR YOUTH - Dr. Hayder Sadeq Makki; Laith Ali Mohammed (Galaxy International Interdisciplinary Research Journal, 2024)
The importance of the research lies in the researchers’ endeavor to use plyometric exercises to develop explosive power, which constitutes an essential core for the technical performance of the backhand smash skill, in addition to achieving accuracy in performance by developing the explosive power of the legs to reach the highest possible height to hit the ball, thus achieving the best performance. In the game of volleyball, the problem of the research was following up on the latest developments in the game of volleyball in general and the development occurring in the skill of the backhand smash in particular at the global, Arab and local levels and because of its impact in deciding the outcome of the match. Through observation, the researchers noted that this skill’s technical level is inconsistent with the development taking place. There is a weakness and significant fluctuation among young players in the level of accuracy of performance, and the researchers attribute this to the weakness in the explosive power of the legs, which is the basis for this skill, and since the skill of crushing from the back area depends in its performance on explosive power, and to find appropriate solutions, the researchers prepared plyometric exercises to develop Developing the explosive power of the legs and thus developing the skill of smashing from the backcourt in volleyball. The objectives of the research are to prepare plyometric exercises to develop explosive power and some biomechanical variables and the accuracy of smashing from the backcourt in volleyball for youth, and to identify the statistical differences between the pre- and post-test of the explosive power of the legs. Identifying the statistical differences between the pre-test and post-test for some biomechanical variables. Identifying the statistical differences between the pre-test and post-test for the accuracy of striking from the back area in volleyball for youth. The researchers used the experimental approach with a single group design as it is the most appropriate for such a study. As for the research population and sample, the researchers determined The research community, using the intentional method, represents the players of the Specialized Volleyball Center in Shatrah District in Dhi Qar Governorate (youth category), aged (16-18) years, numbering (13) players. (5) players were selected from the research community and outside the sample to conduct the experiment. The survey and (8) players represented the research sample, which was the sample percentage(61.53%) from the original community, and one of the most important conclusions is the development of the level of accuracy of the back-slamming skill among members of the research sample through the differences that appeared in the results of the post-test and in favor of the experimental group.